Is corporate social responsibility associated with lower wages? - Karine Nyborg; Tao Zhang (University of Oslo, Department of Economics, 2011)
Firms with a reputation as socially responsible may have an important cost advantage: If workers prefer their employer to be socially responsible, equilibrium wages may be lower in such firms. We explore this hypothesis, combining Norwegian register data with data on firm reputation collected by an employer branding firm. Adjusting for a large set of background variables, we find that the firm's social responsibility reputation is significantly associated with lower wages.
Keywords: C51; D21; D64; Q56; 330; Self-regulation; wage differentials; CSR